5‐Hydroxymethylcytosine Profiles of cfDNA in Urine as Diagnostic, Differential Diagnosis and Prognostic Markers for Multiple Myeloma - Weiwei Xie; Xuehui Li; Hangyu Chen; Jinlin Chu; Lei Zhang; Bo Tang; Wenrong Huang; Linlin Li; Jian Lin; Yujun Dong (Cancer Medicine)
ABSTRACT Background An effective urine‐based method for the diagnosis, differential diagnosis and prognosis of multiple myeloma (MM) has not yet been developed. Urine cell‐free DNA (cfDNA) carrying cancer‐specific genetic and epigenetic aberrations may enable a noninvasive “liquid biopsy” for diagnosis and monitoring of cancer. Methods We first identified MM‐specific hydroxymethylcytosine signatures by comparing 64 MM patients, 23 amyloidosis (AM) patients and 59 healthy cohort. Then, we applied a machine learning algorithm to develop diagnostic and differential diagnosis model. Finally, the prognosis of MM patients was predicted based on their survival time at the last follow‐up. Results We identified 11 5hmC markers using logistic regression algorithm could effectively diagnosis MM (AUC = 0.902), and achieved 85.00% specificity and 85.71% sensitivity. These 11 markers could also effectively differential diagnosis MM (AUC = 0.805) with 88.89% specificity and 73.08% sensitivity. In addition, the prognostic prediction model also effectively predicted the prognosis of patients with MM (p < 0.01), of which 4 differential markers (RAPGEF2, BRD1, TET2, TRAF3IP2) could independently predict the prognosis of MM. Conclusions Together, our findings showed the value of urine cfDNA hydroxymethylcytosine markers in the diagnosis, differential diagnosis and prognosis of MM. Meantime, our study provides a promising and completely non‐invasive method for the diagnosis, differential diagnosis and prognosis prediction of MM.